Reporting quality of randomised controlled trials published in prosthodontic and implantology journals. (1st July 2015) - Kloukos, D.; Papageorgiou, S. N.; Doulis, I.; Petridis, H.; Pandis, N.
Summary: The purpose of this study was to examine the reporting quality of randomised controlled trials (RCTs) published in prosthodontic and implantology journals. Thirty issues of nine journals in prosthodontics and implant dentistry were searched for RCTs, covering the years 2005–2012: The Journal of Prosthetic Dentistry, Journal of Oral Rehabilitation, The International Journal of Prosthodontics, The International Journal of Periodontics & Restorative Dentistry, Clinical Oral Implants Research, Clinical Implant Dentistry & Related Research, The International Journal of Oral & Maxillofacial Implants, Implant Dentistry and Journal of Dentistry . The reporting quality was assessed using a modified Consolidated Standards of Reporting Trials (CONSORT) statement checklist. Data were analysed using descriptive statistics followed by univariable and multivariable examination of statistical associations ( α = 0·05). A total of 147 RCTs were identified with a mean CONSORT score of 69·4 (s.d. = 9·7). Significant differences were found among journals with the Journal of Oral Rehabilitation achieving the highest score (80·6, s.d. = 5·5) followed by Clinical Oral Implants Research (73·7, s.d. = 8·3). Involvement of a statistician/methodologist was significantly associated with increased CONSORT scores. Overall, the reporting quality of RCTs in major prosthodontic and implantology journals requires improvement. This is of paramount importance considering that optimal reporting of RCTs is an important prerequisite for clinical decision‐making.